2005
DOI: 10.1111/j.1365-2044.2005.04297.x
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of families when a relative is diagnosed brain stem dead: understanding of death, observation of brain stem death testing and attitudes to organ donation

Abstract: SummaryBrain stem death may be a difficult concept for relatives to understand. Our ITU practice follows published recommendations that the use of explanatory leaflets showing CT scans and observing brain stem death testing in some cases may help relatives to understand that death has occurred. Using this strategy, we interviewed 27 relatives 12 months after bereavement following certification by brain stem testing, investigating their understanding of brain stem death, subsequent attitudes to organ donation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 13 publications
3
59
1
2
Order By: Relevance
“…Important influences on consent to donation were identified as including prior knowledge of the patients' views, having more contact with requesting staff, viewing the requestor as sensitive to their needs and experiencing an optimal request pattern, which corresponds with the findings of qualitative interview studies with families in the UK. [109][110][111] Black families in the USA, as in the UK, are less likely to consent to donation. A study by Siminoff et al, 112 based on a chart review at nine trauma hospitals in the USA, indicated that non-consent was partly linked with families' experiences of care, with black families less likely to have spoken with an organ procurement representative, being given fewer opportunities to consider the decision with a health-care provider, and having less knowledge of their family members wishes, while they also expressed less favourable attitudes to donation and the health-care system.…”
Section: Introductionmentioning
confidence: 99%
“…Important influences on consent to donation were identified as including prior knowledge of the patients' views, having more contact with requesting staff, viewing the requestor as sensitive to their needs and experiencing an optimal request pattern, which corresponds with the findings of qualitative interview studies with families in the UK. [109][110][111] Black families in the USA, as in the UK, are less likely to consent to donation. A study by Siminoff et al, 112 based on a chart review at nine trauma hospitals in the USA, indicated that non-consent was partly linked with families' experiences of care, with black families less likely to have spoken with an organ procurement representative, being given fewer opportunities to consider the decision with a health-care provider, and having less knowledge of their family members wishes, while they also expressed less favourable attitudes to donation and the health-care system.…”
Section: Introductionmentioning
confidence: 99%
“…Organ donation is an esteemed virtue in society that might subsequently change the behavior of others in the community who interact with the surviving family [105][106][107][108][109][110][111][112]. The conceptual idea of leaving a legacy can provide some further solace for those searching for meaning in the aftermath of a family member's death [113][114][115][116]. The full explanation remains unknown and would be difficult to explore through clinical trials, survey studies, qualitative research, or other approaches that depend on voluntary participation of bereaved children.…”
Section: Discussionmentioning
confidence: 99%
“…One study examined the value of families' observing bedside testing of brain function to help them understand that death had taken place [14]. Yet, for some, their own preestablished belief whether death had already occurred took over.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%